Enhancing energy bars with microalgae: A study on nutritional, physicochemical and sensory properties - Fabio Fanari; Josep Comaposada; Fatma Boukid; Elia Climent; Anna Claret Coma; Luis Guerrero; Massimo Castellari (Journal of Functional Foods, 2023)
Energy bars are popular meal supplements due to their convenience and high nutritional content. Microalgae, such as Spirulina and Chlorella Vulgaris, are appealing food ingredients containing high-quality proteins and essential bioactive compounds. This study investigated the incorporation of these microalgae into a simple energy bar model at three levels of addition (0.0 %, 2.5% and 5.0%). Bars were characterized in terms of colour, water activity, moisture content, texture as well as nutritional and sensory profiles. Results showed that microalgae improved the protein and vitamin B12 content, and influenced color, flavor, and texture of the final product. Spirulina provided the most significant changes, increasing dark green colour, sea/fishy flavours and candies and grass tastes. Chlorella offered different colourways depending on the strain and brought to the sensory profile some umami/fishy notes that need to be taken into account in the formulation of commercial products.